Pengaruh Iklim terhadap Perkembangan Penyakit Layu Fusarium pada Cabai di Beberapa Topoklimat di Yogyakarta - Rachmad Gunadi (Universitas Gadjah Mada, 1997)
The widespread of chilli cultivation and its serious damage caused by Fusarium wilt was observed to study the weather characters of 3 topoclimates in Yogyakarta and their support on the disease development. The result of the study shows that the altitude gradient gives specific effect to weather conditions and this condition shows the specific effect on disease development. The macro elements of weather tends to be more significantly different between topoclimates than the micro ones. The optimal altitude for disease development is around 400 m. Relative humidity and rainfall show the dominant effect on disease development beside of air and soil temperatures. The range of weather condition needed by F. oxysporum for survival tends to be much wider than the range needed for disease development.